Two new species of Apodopsyllus (Copepoda, Harpacticoida) from Jeju Island, Korea - Back, Jinwook; Lee, Wonchoel (Zootaxa, 2012)
A study of harpacticoid copepods from the intertidal zone of Jeju Island in the South Sea of Korea resulted in the discovery of two new paramesochrid species. They are placed in the genus Apodopsyllus Huys, 2009 on account of the following combination of characters: the absence of P2–P4 endopods, the poorly defined body segmentation, the two-segmented P1 endopod and exopod, and the fusion of the P2-P4 coxae with the respective body somites. Apodopsyllus gwakjiensis sp. nov. is most closely related to A. bermudensis (Coull & Hogue, 1978), but clearly distinguishable from it by the following characters: the concave shape of the baseoendopod with two bare setae, P4 basis without endopodal seta, and certain detailed characteristics of the mouthparts. Apodopsyllus unisetosus sp. nov. is easily distinguished from its congeners by the antennary exopod, which is armed with a single apical seta. In addition, A. unisetosus has the baseoendopod of P5 fused with somite, the P1 armed with one inner and one outer basal seta, and the unique shape of the male P6. Keys to genera of the family Paramesochridae Lang, 1944, as well as to species of the genus Apodopsyllus Huys, 2009 are provided.